ISSUES OF EDUCATION, KNOWLEDGE, AND ETHICS IN ANBAR OTIN'S WORKS - Dilfuza Ganievna Rashidova (Western European Studies, 2025)
This article explores the perspectives of the enlightenment poet Anbar Otin on the education and moral views of Turkestan women, as well as the social paradigms regarding women's access to education. The author highlights how the philosopher-poet Anbar Otin, in her works, examined various ideological currents, religious, moral, and socio-philosophical views in an interconnected manner. The study also emphasizes the relevance of the issues she addressed to contemporary society
Keywords: Anbar Otin; enlightenment thinkers; poet; scholars